GREEN WALL VENTILATION BLOCK BERBAHAN DAUR ULANG UNTUK ARSITEKTUR TROPIS BERKELANJUTAN - Harry Wibowo; Siti Zulfa Yusni; Zhilli Izzadati Khairuni; Rafika Hilmi Nasution; Ahmad Zulfikar; Kharunnisak Kharunnisak; Denny Meisandy Hutauruk (Jurnal Arsitektur ARCADE, 2025)
Abstract: This research develops a Green Wall Ventilation Block made from recycled plastic and glass as an innovative sustainable façade solution for tropical architecture. The study aims to design a modular ventilation block capable of supporting natural airflow while providing planting space for green wall systems. The research method integrates digital modeling using SketchUp, airflow simulation through Autodesk Vasari, formulation of recycled composite material, and fabrication of a full-scale 1:1 prototype using a combined 3D printing and fiberglass mold. Simulation results confirm that the diagonal ventilation geometry improves airflow velocity and stability under tropical climatic conditions, while the planter cavity remains functional without obstructing ventilation. The recycled plastic–glass composite demonstrates good workability, reduced density, and sufficient durability for non-structural façade applications. The final prototype shows precise geometry, structural stability, and compatibility for modular installation as a green façade. Overall, the developed system not only enhances passive ventilation and thermal performance but also contributes to reducing plastic and glass waste by repurposing them into functional architectural components. This innovation offers strong potential for wider implementation in sustainable tropical building design. Keyword: Green Wall; Recycled Materials; Ventilation Block Abstrak: Penelitian ini mengembangkan Green Wall Ventilation Block berbahan limbah plastik dan kaca sebagai solusi fasad berkelanjutan untuk arsitektur tropis. Tujuan penelitian adalah merancang modul ventilasi yang mampu mendukung aliran udara alami sekaligus menyediakan ruang tanam bagi sistem green wall. Metode penelitian mengintegrasikan pemodelan digital menggunakan SketchUp, simulasi aliran udara melalui Autodesk Vasari, formulasi material komposit berbahan daur ulang, serta pembuatan prototipe skala 1:1 menggunakan cetakan gabungan 3D printing dan fiberglass. Hasil simulasi menunjukkan bahwa geometri bukaan diagonal meningkatkan stabilitas dan kecepatan aliran udara pada kondisi iklim tropis, sementara ruang tanam tetap berfungsi tanpa menghalangi ventilasi. Material komposit plastik–kaca menghasilkan densitas lebih ringan, mudah dicetak, dan cukup kuat untuk aplikasi fasad non-struktural. Prototipe akhir memiliki presisi tinggi, stabil secara struktural, dan dapat disusun secara modular sebagai green façade. Secara keseluruhan, sistem ini tidak hanya meningkatkan ventilasi pasif dan kinerja termal bangunan, tetapi juga berkontribusi pada pengurangan limbah plastik dan kaca melalui pemanfaatan kembali sebagai material konstruksi. Inovasi ini memiliki potensi besar untuk diterapkan lebih luas pada desain bangunan tropis berkelanjutan. Kata Kunci: Green Wall; Material Daur Ulang; Ventilation Block